Relationship among core competency, self-efficacy and transition shock in Chinese newly graduated nurses: a cross-sectional study - Ting Wang; Shuping Tong; Lan Xu; Yahui Tong; Zhaofang Tang; Lifen Mao; Xiaoqing Shi (BMJ Open, 2024)
Objectives To investigate how core competency and self-efficacy of newly graduated nurses affect their experience of transition shock, and to determine the relationship between these factors.Design A cross-sectional study.Methods 262 newly graduated nurses participated in a cross-sectional study by using demographic data, the transition shock scale, the competency inventory for registered nurses scale and the self-efficacy scale.Results Among newly graduated nurses, the score of transition shock was 77.641±24.140, the score of core competency was 125 (109.5, 163.5) and the score of self-efficacy was 2.5 (2,3), all of which were at a moderate level. The core competency and self-efficacy of the newly graduated nurses had a negative impact on the transition shock (β=−0.151, p=0.026; β=−0.379, p<0.001). Additionally, self-efficacy played a mediating role in the relationship between core competency and transition shock, with a mediating effect accounting for 57.34% of the total effect.Conclusions The transition shock of newly graduated nurses was at a moderate level, with the highest level of transition shock occurring within the first year of employment. Self-efficacy plays a mediating role in the relationship between core competency and transition shock. Nursing managers should create standardised training for newly graduated nurses within the first year of employment to reduce their transition shock. This will help improve newly graduated nurses’ core competency, enhance self-efficacy and support the graduates. This will alleviate the impact of transition shock on newly graduated nurses, helping them transition smoothly and successfully.